2012
DOI: 10.1097/ta.0b013e318270d572
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a novel trauma score

Abstract: Prognostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
0
18
0
2
Order By: Relevance
“…The first pre-hospital assessment was used; if missing; assessment on admission was used 53.5%* Pupil size Three categories according to the Eppendorf-Cologne Scale [ 12 ]: normal, anisocoria, and bilateral dilated. The first pre-hospital assessment was used; if missing; assessment on admission was used 54.9%* Motor function The motor function was derived from the Glasgow Coma Store (GCS) motor score according to the Eppendorf-Cologne scale [ 12 ]: normal (6 points in GCS); directed (4-5); non-directed (2-3), and none (1). The first pre-hospital assessment was used if available; if missing assessment on admission was used in non-intubated cases 2.7% Mechanism Blunt or penetrating mechanism of injury 6.1% Blood pressure Systolic blood pressure (mmHg), first measurement after admission; in case of missing values the first pre-hospital measurement was used 10.7% Coagulation: INR International normalized ratio (INR); first measurement after admission 12.9% Acidosis: base deficit Base deficit, or base excess (mEq/l); first measurement after admission 46.0% Blood: haemoglobin Haemoglobin (g/dl); first measurement after admission 7.6% CPR Cardiopulmonary resuscitation (CPR), performed pre-hospitally in case of cardiac arrest (not in the emergency room) 3.2% *Actually not part of the reduced data collection form used in 47.4% of cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first pre-hospital assessment was used; if missing; assessment on admission was used 53.5%* Pupil size Three categories according to the Eppendorf-Cologne Scale [ 12 ]: normal, anisocoria, and bilateral dilated. The first pre-hospital assessment was used; if missing; assessment on admission was used 54.9%* Motor function The motor function was derived from the Glasgow Coma Store (GCS) motor score according to the Eppendorf-Cologne scale [ 12 ]: normal (6 points in GCS); directed (4-5); non-directed (2-3), and none (1). The first pre-hospital assessment was used if available; if missing assessment on admission was used in non-intubated cases 2.7% Mechanism Blunt or penetrating mechanism of injury 6.1% Blood pressure Systolic blood pressure (mmHg), first measurement after admission; in case of missing values the first pre-hospital measurement was used 10.7% Coagulation: INR International normalized ratio (INR); first measurement after admission 12.9% Acidosis: base deficit Base deficit, or base excess (mEq/l); first measurement after admission 46.0% Blood: haemoglobin Haemoglobin (g/dl); first measurement after admission 7.6% CPR Cardiopulmonary resuscitation (CPR), performed pre-hospitally in case of cardiac arrest (not in the emergency room) 3.2% *Actually not part of the reduced data collection form used in 47.4% of cases.…”
Section: Resultsmentioning
confidence: 99%
“…Both aspects are easy to assess and have been recorded since the foundation of the registry. However, only recent analyses showed that their predictive ability was even better than the GCS [ 12 - 14 ]. They independently added prognostic information to the prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…Considering prognostic models in TBI, level of consciousness and pupil status represent major predictive features as recently demonstrated by the GCS-P as a novel score 10,20 . This has also been modeled as ECS using pupil reactivity, size and modified motor score 11,21 . However, in aSAH, pupil status in particular has rarely been integrated in prognostic models and grading systems even though it represents an easy assessable feature and pupil reactivity has already been associated with long-term outcome in poor-grade aSAH patients 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Since GCS-P and ECS demonstrated good predictive performance in TBI, we evaluated the prognostic utility of these novel trauma scores for aSAH 10,11 . In comparison to GCS, GCS-P allowed further subclassification of GCS grade 3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality in patients with severe TBI was higher than among the ones mild TBI in some studies 28,29 . However, we did not find such difference in the present study.…”
Section: Discussionmentioning
confidence: 88%